Disclosing the truth: a dilemma between instilling hope and respecting patient autonomy in everyday clinical practice - Sarafis, Pavlos; Tsounis, Andreas; Malliarou, Maria; Lahana, Eleni (My University, 2014)
Background: While medical ethics place a high value on providing truthful information to patients, disclosure practices are far from being the norm in many countries. Transmitting bad news still remains a big problem that health care professionals face in their every day clinical practice. Aims: Through the review of relevant literature, an attempt to examine the trends in this issue worldwide will be made. Method: Various electronic databases were searched by the authors and through systematic selection 51 scientific articles were identified that this literature review is based on. Results: There are many parameters that lead to the concealment of truth. Factors related to doctors, patients and their close environment, still maintain a strong resistance against disclosure of diagnosis and prognosis in terminally ill patients, while cultural influences lead to different approaches in various countries. Withholding the truth is mainly based in the fear of causing despair to patients. However, fostering a spurious hope, hides the danger of its’ total loss, while it can disturb patient-doctor relationship.
Keywords: Disclosure; Truth; Autonomy; Cultural influences; Ethics; Hope; Cancer